PENINGKATAN PENGETAHUAN SISWA MENGENAI PRODUK INDUSTRI MELALUI PENGENALAN KONSEP CAPSTONE DESIGN PROJECT - Bonitasari Nurul Alfa; Mega Purnamasari; Diah Utami (Politeknik 'Aisyiyah Pontianak, 2024)
Project-based learning is considered important for developing student character because it provides students with the opportunity to learn through experience (experiential learning). The Project-based Learning (PjBL) model is a learning model that involves students' activeness in solving problems, carried out in groups/independently through scientific stages with certain time limits which are outlined in a product to then be presented to others. Starting from 2022 to 2024, the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) provides three curriculum options that can be applied by educational units in learning, namely the 2013 curriculum, emergency curriculum and prototype curriculum. The prototype curriculum has been implemented in 2,500 educational units that are members of the Driving Schools and Center of Excellence Vocational Schools program in 2021. However, starting in 2022, educational units that are not included in driving schools will also be given the option to be able to implement the prototype curriculum. The capstone project is a culmination of the learning process by applying what has been learned in the learning process. Innovation and product development is something that companies rely on to be able to progress and compete in the industrial world. Industrial products will ultimately be produced in a manufacturing system where everything becomes more complex. Insight and knowledge regarding capstone design projects through training to introduce the stages of the product and system development process. Community Service activities have been carried out with vocational school student participants showing enthusiasm and increased knowledge regarding the capstone design project.